CARUMONAM IN COMPLICATED URINARY TRACT INFECTIONS - WATANABE, HIRONOBU; FUJITA, YUKITOSHI; MATSUMOTO, SHIGERU; SUGITA, OSAMU (CHEMOTHERAPY, 1987)
Carumonam, a new monobactam antibiotic, was investigated for antibacterial activity, absorption and excretion, clinical evaluation and side effects. The results obtained were as follows: 1) Antibacterial activity of carumonam againstPseudomonas aeruginosawas equal to that of cefoperazone. Antibacterial activity of carumonam againstEscherichia coli, Serratia marcescens, Proteus mirabilis, Proteus vulgaris, andKlebsiella pneumoniaewas superior to that of cefoperazone. Antibacterial activity againstE. coli, S. marcescens, P. mirabilis, P. vulgaris, K. pneumoniae, P. aeruginosawas almost equal to that of aztreonam. 2) Carumonam 1 g was administered by 30 min and by 1 h i. v. drip infusion to three healthy volunteers by a cross-over method. The maximum serum levels of carumonam after 30 min i. v. drip infusion was 88.6±16.2μg/ml, and the maximum serum levels after 1 h i.v. drip infusion was 67.1±8.8μg/ml. 3) Two patients with complicated urinary tract infections were treated with carumonam and good results were obtained in both cases. 4) Adverse reactions were evaluated in five cases; but the only side effects observed were slight increase in eosinophils in two cases, and slight increase of transaminase in one case.